2022
DOI: 10.29100/jipi.v7i1.2498
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul Kimia Pada Materi Struktur Atom Untuk Meningkatkan Hasil Belajar

Abstract: 3) ABSTRAKPelaksanaan pembelajaran Kimia di SMA secara online di masa pandemi menimbulkan permasalahan penyerapan materi. Oleh sebab itu, penelitian ini dilakukan dengan dasar tujuan pengembangan e-modul Kimia khususnya materi struktur atom untuk memaksimalkan penyerapan materi oleh siswa sehingga dapat meningkatkan hasil belajar siswa. Model pengembangan yang digunakan yaitu 4D model (Define, Design, Development, and Diseminate). Untuk mengukur kelayakan dari e-modul yang disusun dilakukan proses validasi ahl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
4
0
4
Order By: Relevance
“…The SRL questionnaire results showed that the average value of the experimental class was higher than that of the control class. The results of this research are following the research that has been carried out by Gevi & Andromeda (2019) and Mufida et al (2022) that the emodule equipped with videos, animations, images, and questions provided makes the characteristics of the emodule as self-instruction function properly, namely students take the initiative to learn independently not depending on others, especially educators. In addition to making students independent of learning, e-modules equipped with multiple representations can motivate and shorten the learning time of students because representation can bridge the student's process in understanding the concept of buffer solutions (Dewi et al, 2021;Hurrahman et al, 2022;Wiyarsi, Sutrisno, & Rohaeti, 2018).…”
Section: Implementation Of Multiple Representation-based E-modulessupporting
confidence: 70%
“…The SRL questionnaire results showed that the average value of the experimental class was higher than that of the control class. The results of this research are following the research that has been carried out by Gevi & Andromeda (2019) and Mufida et al (2022) that the emodule equipped with videos, animations, images, and questions provided makes the characteristics of the emodule as self-instruction function properly, namely students take the initiative to learn independently not depending on others, especially educators. In addition to making students independent of learning, e-modules equipped with multiple representations can motivate and shorten the learning time of students because representation can bridge the student's process in understanding the concept of buffer solutions (Dewi et al, 2021;Hurrahman et al, 2022;Wiyarsi, Sutrisno, & Rohaeti, 2018).…”
Section: Implementation Of Multiple Representation-based E-modulessupporting
confidence: 70%
“…Penggunaan bahan ajar berupa E-modul dapat mendukung peserta didik agar lebih mandiri dan aktif (Herawati & Muhtadin, 2018). E-modul digunakan dalam pembelajaran mampu meningkatkan keterampilan pemecahan masalah (Zhafirah et al, 2021), dan hasil belajar dari peserta didik (Mufida et al, 2022).…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan pernyataan Mufida, dkk (2022) yang menjelaskan bahwa "peserta didik masih mengalami kesulitan dalam memahami materi struktur atom". Berdasarkan pertanyaan 4, dapat diketahui bahwa semua peserta didik mempunyai smartphone android atau laptop, yang digunakan setiap harinya [13]. Hal ini menunjukkan bahwa pengembangan media google slide bisa digunakan sebagai alternatif media yang dapat diakses dengan mudah dan tanpa batas waktu [11].…”
Section: Hasil Dan Pembahasan Pengembangan Media Google Slide Tahap A...unclassified